A guanidinium modified rhodamine-based fluorescent probe for in vitro/vivo imaging of gold ions1. Issue 19 (7th October 2015) - Karakuş, Erman; Cakan-Akdogan, Gulcin; Emrullahoğlu, Mustafa
<x xml:space="preserve">Abstract</x> We devised a rhodamine-based fluorescent probe functionalized with a guanidinium moiety, which both operates efficiently in pure aqueous media and displays a selective fluorescence response to Au3+ ions.